Cover Feature: Multistimuli‐Responsive Materials from Benzothiadiazole‐Based Charge‐Transfer Chromophores: Interdependence of Optical Properties and Aggregation (ChemPhotoChem 12/2018). Issue 12 (6th December 2018) - Bardi, Brunella; Dall'Agnese, Chunxiang; Tassé, Marine; Ladeira, Sonia; Painelli, Anna; Moineau‐Chane Ching, Kathleen I.; Terenziani, Francesca
Abstract : The Cover Feature illustrates the effects of the application of soft external stimuli on powders or films of quadrupolar organic dyes: The relative alignment of the molecules is affected, favouring either J‐aggregrates, H‐aggregrates or even other forms not predicted by the exciton pictures. The emission spectrum varies accordingly, covering a large part of the visible range. More information can be found in the Article by B. Bardi et al. onpage 1027 in Issue 12, 2018 (DOI:10.1002/cptc.201800145 ).